Про розв'язність задачі Діріхле для еліптичних недивергентних рівнянь другого порядку в області з конічною точкою - Борсук, М.В. (Український математичний журнал, 1996)
We study the problem of solvability of the Dirichlet problem for second-order linear and quasilinear uniformly elliptic equations in a bounded domain whose boundary contains a conical point. We prove new theorems on the unique solvability of a linear problem under minimal smoothness conditions for the coefficients, right-hand sides, and the boundary of the domain. We find classes of solvability of the problem for quasilinear equations under natural conditions.